Pengaruh Return on Aset Terhadap Harga Saham: Studi Pada Perusahaan Makanan dan Minuman - Laia, Nyawarman; Sianipar, Milka Rositi (Jurnal Ekonomi Bisnis Digital, 2023)
Tough competition in the food and beverage industry requires innovative strategies to increase productivity and attract new capital from the capital markets. Healthy company performance will generate a lot of profit for the company, so that the company's share price will also increase and attract the interest of investors. This study aims to analyse the impact of return on assets on the share price of food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2021. The population of this study was 19 companies in the food and beverage sector listed on the IDX for the 2019-2021 period, which were accessed from the website www.idx.co.id. Purposive sampling technique was used to determine the sample, and data from 57 companies were obtained. Simple linear regression is used in the modelling after the results of the classical assumption test show that the data are normally distributed, there is no multicollinearity problem and no heteroscedasticity. It can be concluded that this model has met the requirements of the classical assumption test in the use of multiple linear regression models. The test results show that Fcount (2.423) is less than the Ftable (3.947) and the significance is less than 0.05, it can be concluded that RoA has an effect on stock prices.